Safety outcomes of new versus old generation transcatheter aortic valves. Issue 1 (13th December 2018) - Finkelstein, Ariel; Rozenbaum, Zach; Zhitomirsky, Sophia; Halkin, Amir; Banai, Shmuel; Bazan, Samuel; Barbash, Israel; Segev, Amit; Guetta, Victor; Danenberg, Haim; Planner, David; Orvin, Katia; et al.
Abstract: Objective: To compare procedural outcomes of transcatheter aortic valve implantation (TAVI) patients who were implanted with older versus newer generation valves. Background: The current evidence base for improved safety of the newer commercially available TAVI valves is limited. Methods: A retrospective analysis of the Israeli multicenter TAVI registry was performed. Patients were stratified by valve generation of four commercially available devices: Edwards Sapien (ESX) Edwards Sapien S3 (ES3), Medtronic CoreValve (MCV), and Medtronic Evolut R (MER). Results: The cohort consisted of 737 patients with new generation valves (NGVs; ES3 n = 223; MER n = 514) and 1, 869 with old generation valves (OGVs; MCV n = 1, 181; ESX n = 688). Device success rates were significantly higher in NGV (97.5 versus 95.4%), with less post‐procedural paravalvular leak (3 versus 5.8%), and valve mal‐positioning (1.2 versus 3.4%); all P ‐values<0.05. There were no differences in rates of permanent pacemaker implantation, stroke or acute kidney injury (AKI) of any stage between the groups, although stage ≥2 AKI was more prevalent in NGV. After adjustment to significant differences in baseline patient and procedural characteristics, device success was higher (OR 1.86, 95% confidence interval (CI) 1.09–3.18, P = 0.023) and the 1‐month safety outcome was significantly lower (OR 0.72, 95% CI 0.55–0.96, P = 0.025) for NGV. Device success was driven mainly by improved rates of PVL of ES3, while the safety outcome was mainly driven by improved rates of life‐threatening bleeding and valve mal‐positioning of MER. Conclusion: As compared to OGV, use of NGV for TAVI was associated with higher rates of device success and lower rates of adverse events.